Strengthening National Health Systems for Improving Efficiency of Health Service Delivery in Nepal - Shakya, H S; Adhikari, S; Gurung, G; Pant, S; Aryal, S; Singh, A B; Sherpa, M G (Journal of Nepal Health Research Council, 2012)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> The success of Nepalâ€™s community-based health programmes in promoting maternal and child health has been achieved due to an overall improvement in service delivery facilities and health support systems. This article assesses the progress made by the Government of Nepal in improving health service delivery by introducing three key components: an improved health logistics management, facility-based maternal and neonatal health services, and decentralized health facility management. <span style="font-size: 12.0pt; line-height: 115%; font-family: ";Times New Roman";,";serif";; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Â Keywords: facility-based maternal and neonatal health services; health logistics system; local health governance.<!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>